Genome-wide identification and analysis of the EIN3/EIL gene family in broomcorn millet (Panicum miliaceum L.) - Yang, Mengke; Song, Xiaohan; Li, Jiazhen; Wang, Shiji; Zhang, Meichun; Deng, Xin; Wang, Hongyan (Frontiers in Plant Science, 2024)
The EIN3/EIL gene family holds a pivotal role as it encodes a crucial transcription factor in plants. During the process of polyploidization in broomcorn millet (Panicum miliaceum L.), there is an intriguing above-average amplification observed within the EIN3/EIL gene family. Nonetheless, our current knowledge of this gene family in broomcorn millet remains limited. Hence, in this study, we conducted a comprehensive analysis of the EIN3/EIL gene family in broomcorn millet, aiming to provide a deeper understanding of the potential evolutionary changes. Additionally, we analyzed the EIN3/EIL gene family of Panicum hallii L., a close relative of broomcorn millet, to enhance our characterization efforts. Within this study, we identified a total of 15 EIN3/EIL genes specific to broomcorn millet. Through covariance analysis, it was revealed that all PmEIL genes, except PmEIL1 and PmEIL15, had duplicate copies generated through genome-wide duplication events. Importantly, the Ka/Ks values of all duplicated genes were found to be less than 1, indicating strong purifying selection. Phylogenetic analysis showed that these genes could be categorized into four distinct evolutionary branches, showcasing similar characteristics among members within the same branch. However, there appeared to be an uneven distribution of cis-acting elements amid the EIN3/EIL genes. Further examination of transcriptomic data shed light on the diverse spatiotemporal and stress-related expression patterns exhibited by the EIN3/EIL genes in broomcorn millet. Notably, under cold stress, the expression of PmEIL3/4/8/14 was significantly up-regulated, while under drought stress, PmEIL4/5/6 displayed significant up-regulation. Intriguingly, the expression pattern of PmEIL15 showed an opposite pattern in resistant and sensitive cultivars. The findings of this study augment our understanding of the EIN3/EIL gene family in broomcorn millet and offer a valuable reference for future investigations into polyploid studies. Moreover, this study establishes a theoretical foundation for further exploration of the ethylene signaling pathway in broomcorn millet.